Lung model parameter estimation by unscented Kalman filter - Akan, Aydın; SAATÇI, ESRA (IEEE, 345 E 47TH ST, NEW YORK, NY 10017 USA, 2007)
Dynamic nonlinear models are the best choice to analyze respiratory systems and to describe system mechanics. In this work, Unscented Kalman Filtering (UKF) was used to estimate the dynamic nonlinear model parameters of the lung model by using the measured airway flow, mask pressure and integrated lung volume. Artificially generated data and the data from Chronic Obstructive Pulmonary Diseased (COPD) patients were analyzed by the proposed model and the proposed UKF algorithm. Simulation results for both cases demonstrated that UKF is a promising estimation method for the respiratory system analysis.
Keywords: nonlinear model; ventilation; doğrusal olmayan model; havalandırma